Navidget for Easy 3D Camera Positioning from 2D Inputs - Hachet, Martin; Decle, Fabrice; Knodel, Sebastian; Guitton, Pascal (3DUI : IEEE Symposium on 3D User Interfaces 2008 : Reno, Nevada, USA, March 8-9, 2008 : proceedings, 2008)
Navidget is a new interaction technique for camera positioning in 3D environments. This technique derives from the point-of-interest (POI) approaches where the endpoint of a trajectory is selected for smooth camera motions. Unlike the existing POI techniques, Navidget does not attempt to automatically estimate where and how the user wants to move. Instead, it provides good feedback and control for fast and easy interactive camera positioning. Navidget can also be useful for distant inspection when used with a preview window. This new 3D User interface is totally based on 2D inputs. As a result, it is appropriate for a wide variety of visualization systems, from small handheld devices to large interactive displays. A user study on TabletPC shows that the usability of Navidget is very good for both expert and novice users. This new technique is more appropriate than the conventional 3D viewer interfaces for some camera positioning tasks in 3D environments.